Ethnobotany of Northern Africa and Levante - Book Review - Solo, Intan Riani; Tungga Dewi, Imelda Zahra; Indah Sari, Anggi Mei (Ethnobotany Research and Applications, 2025)
Ethnobotany of Northern Africa and Levant, edited by Rainer W. Bussmann, Mostafa Elachouri, and Zaal Kikvidze. Springer Nature Switzerland AG, 2024, pp 2.157, €379.99 (Hardcover), €406.59 (eBook), ISBN 9783031397943 (Hardcover), ISBN 9783031431050 (eBook) The book Ethnobotany of Northern Africa and Levante, edited by Rainer W. Bussmann, Mostafa Elachouri, and Zaal Kikvidze, provides a comprehensive analysis of ethnobotanical knowledge across North Africa and the Levant. This scholarly work, part of the Ethnobotany of Mountain Regions series, explores the intricate relationships between communities and their botanical environments within culturally and ecologically diverse landscapes. It offers significant insights into traditional ethnobotanical practices, medicinal plants, and contemporary issues of conservation and sustainable development.